Patients with chronic rhinosinusitis and obstructive sleep apnea have increased paroxysmal limb movement. Issue 2 (March 2018) - Mahdavinia, Mahboobeh; Hui, Jessica W.; Zitun, Mohamed; Lastra, Alejandra; Herdegen, James J.; Codispoti, Christopher D.; Khan, Rafsa J.; LoSavio, Phillip S.; Batra, Pete S.
Background: Patients with chronic rhinosinusitis (CRS) frequently experience sleep disruption and are at a higher than normal risk for obstructive sleep apnea (OSA). The purpose of this study was to determine how CRS affects polysomnography findings and sleep-related breathing in OSA. Methods: A cohort study was performed that included 107 adult patients with CRS and comorbid OSA (CRS+OSA group) and 137 patients with OSA and without CRS as the control group. An electronic medical records database was used to identify eligible subjects. Comorbid conditions and polysomnography data were compared between the two groups by using logistic and linear regression analyses. Results: A total of 246 patients were included: 107 patients in the CRS+OSA group and 137 patients with OSA and without CRS in the control group. After adjusting for demographic factors, the patients in the CRS+OSA group had a lower body mass index (BMI) and higher age at the time of diagnosis of OSA (p < 0.001). The patients in the CRS+OSA group had higher odds of having asthma and eczema. There was an increase in the periodic limb movement (PLM) index in the CRS+OSA group. Apnea and hypopnea indices were similar in the two groups. Conclusion: Patients with CRS developed OSA at a lower BMI; patients CRS and OSA had similar sleep-related breathing patterns but higher risks for PLMs compared with patients with OSA and without CRS.